Chapter 19: Becoming sanfei: the irregularization of foreign migrants in China - Haugen, Heidi Østbø (Edward Elgar Publishing, 2023)
This chapter explores the fuzzy boundaries of who is an irregular migrant in China, and how the latent threat of being cast as irregular influences the lives of migrants. The shorthand for irregular migration in China is "three illegals" (san fei), which comprises unlawful entry, residence, and work. Drawing upon data about different groups of migrants in China, including traders, students, marriage migrants, and returnees, the chapter discusses how foreigners in China are continuously at risk of having their status changed from "legal" to "illegal". This transition can result from national or local changes in law enforcement or from idiosyncratic events, such as residents reporting migrants in the wake of, for example, conflicts between migrant tenants and landlords or international students and university administrators. Policies and enforcement practices to regulate international migration in the People's Republic of China today build on past and current methods to control internal migration.